Muslim-Consumers Behaviour in Willingness to Buy Halal Food in Japan - Inayah Swasti Ratih; Muhammad Dzulfaqori Jatnika; Alfadhila Khairil Sinatrya; Nur Syamsiyah (Sultang Agung Islamic University, 2021)
The purpose of this study is to determine the effect of religiosity, food ingredients, halal label, knowledge, and income on the willingness of Indonesian Muslim consumers in Japan to buy Halal Food Products. The research method used is a quantitative method, using regression analysis tests. The research questionnaire was distributed to respondents who are Indonesian Muslim in Japan. The finding of this research is religiosity and food ingridients has significant influence on consumers' willingness to buy halal food products. Halal label does not have a significant effect on consumers' willingness to buy halal food products. Knowledge does not have significant effect on consumers' willingness to buy halal food products. income does not strengthen the effect of religiosity on consumers' willingness to buy halal food products. Income does not strengthen the influence of Halal label on consumers' willingness to buy halal food products. Income does not strengthen the influence of food ingredients on consumers' willingness to buy halal food products. That income does not strengthen the influence of knowledge on consumers' willingness to buy halal food products. This is first study of behavior Indonesia Muslim in Japan to be minority. The implication is to improve the development strategy of halal food products industry in Japan and to improve understanding and knowledge of halal food products. Limitations in this study is the number of respondents who are relatively few compared to the total Muslims working in Japan and only limited to Indonesian citizens.